Penyalahgunaan Wewenang Notaris dalam Pembuatan Akta: Analisis Celah Hukum dan Lemahnya Pengawasan - Fathurrohman Nur Hidayat; Rendy Aprilio Sulaiman; David Frans Rafael Simorangkir; Rois Faisal Amin; Baidhowi Baidhowi (Jurnal Hukum, Administrasi Publik dan Negara, 2026)
This study aims to analyze the abuse of authority by notaries in the making of authentic deeds, focusing on the forms of misconduct, legal loopholes, and weaknesses in the supervisory system. The research employs a qualitative method with a normative juridical approach through library research, examining laws and regulations, legal doctrines, scholarly literature, and relevant cases related to notarial practice. The findings reveal that abuse of authority occurs due to both negligence and intentional actions. Common forms of misconduct include the failure to verify the authenticity and completeness of supporting documents, the preparation of deeds outside the notary’s authorized jurisdiction, the delegation of notarial duties to unauthorized parties, and the existence of conflicts of interest that compromise impartiality. In addition, legal loopholes arise from ambiguous regulatory provisions, inconsistencies in legal interpretation, and the rapid development of digital technology, particularly electronic transactions and online services, which have not yet been comprehensively regulated. The study also finds that the existing supervisory system remains weak, reactive, and often ineffective in preventing violations before they occur. Therefore, the abuse of notarial authority should be viewed as a systemic issue requiring comprehensive reforms in legal regulations, supervisory mechanisms, professional ethics enforcement, and notarial education to ensure legal certainty, accountability, and the preservation of public trust in the notarial profession.